2006
DOI: 10.3354/ame045207
|View full text |Cite
|
Sign up to set email alerts
|

Trophic cascades mediated by copepods, not nutrient supply rate, determine the development of picocyanobacteria

Abstract: We studied the effect of nutrient supply rate (resources) and concentrations of copepods (top predator) on picocyanbacteria (PCY) in experimental ecosystems (mesocosms) using gradients of both nutrients and predators. The biomass and production of PCY, and the biomass and predation rates of their predators were determined by epifluorescence microscopy, X-ray microanalysis (XRMA), the 14 C method, and cell counting by microscopy. PCY biomass did not change significantly with increased supply of nutrients, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
1
6
1
Order By: Relevance
“…Copepod predation on ciliates even resulted in a stimulation of picocyanobacteria (Sundt-Hansen et al 2006), which is in contrast to our observed effects on heterotrophic bacterioplankton. It suggests that, at the level of picoplankton, where autotrophs such as Synechococcus are generally slightly larger than heterotrophic bacteria, prokaryotic cell sizes determine whether HNF or ciliates are the major grazers and thereby how the cascading zooplankton predation effects will function.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Copepod predation on ciliates even resulted in a stimulation of picocyanobacteria (Sundt-Hansen et al 2006), which is in contrast to our observed effects on heterotrophic bacterioplankton. It suggests that, at the level of picoplankton, where autotrophs such as Synechococcus are generally slightly larger than heterotrophic bacteria, prokaryotic cell sizes determine whether HNF or ciliates are the major grazers and thereby how the cascading zooplankton predation effects will function.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings on the effects of the copepod-mediated trophic cascade on purely heterotrophic microorganisms are consistent with the observed results of size-selective copepod predation on autotrophic plankton, in which the copepod-ciliate linkage also seems to be decisive for food-web structuring: large-sized phytoplankton (e.g., diatoms) become reduced by direct grazing, whereas nano-sized algae are positively correlated to copepods because of topdown control of ciliates (Stibor et al 2004;Sommer and Sommer 2006). Copepod predation on ciliates even resulted in a stimulation of picocyanobacteria (Sundt-Hansen et al 2006), which is in contrast to our observed effects on heterotrophic bacterioplankton. It suggests that, at the level of picoplankton, where autotrophs such as Synechococcus are generally slightly larger than heterotrophic bacteria, prokaryotic cell sizes determine whether HNF or ciliates are the major grazers and thereby how the cascading zooplankton predation effects will function.…”
Section: Discussionsupporting
confidence: 86%
“…Copepods prey selectively and efficiently on ciliates and algae in the size range 20 to 40 µm (Yoshida et al 2001), thereby triggering a trophic cascade, enabling high numbers of HNF and the potential for a greater mortality of Pcy (Zöllner et al 2003). Sundt-Hansen et al (2006) have shown that in marine mesocosms, copepods have a profound structuring effect on the pelagic food web, and thus directly and indirectly, regulate the abundance of Pcy predators. In this way, the strength of the trophic cascade downward to Pcy depends substantially on the structure of the food web and the inventory of zooplankton species present (Gismervik 2006;van Grenberghe et al 2008).…”
Section: Biotic Interactionsmentioning
confidence: 99%
“…In these, the combination of mathematical modeling with mesocosm studies, proved a useful tool to identify principles that underlie the complex dynamics of the marine microbial food web, and to understand how changes in environmental conditions such as increased DOC levels or changes in silicate or mineral nutrient levels might affect marine systems. While previous studies have pinpointed how cascading effects from copepods (Sundt‐Hansen et al ; Zöllner et al ; Löder et al ) together with bottom‐up manipulations (Kuuppo et al 1998; Sommer et al ) control elemental cycling in the microbial food web, the current study represents a case where the microbial food web did not respond much to the differences in N‐source or carbon load, and also less than expected to differences in initial copepod abundances.…”
Section: Discussionmentioning
confidence: 63%